Reconstruct the Memory of Roman Space: Analysis of Federico Fellini’s Cinema - Xie, Fang; Lyu, Dongye (Street Art & Urban Creativity, 2024)
Throughout history, the interplay between cinema and urban environments has played a pivotal role in both reflecting and influencing perceptions of cities and their development. In cinematic narratives, cities often transcend mere backdrops, assuming central roles rich in symbolic meaning, which underscores the significance of urban spaces in shaping cultural narratives. Starting from the films directed by the famous Italian director Federico Fellini, this paper focuses on the process of reproducing the urban space of Rome and organizes the Fellini-style imagination about the Roman space by combing the construction and expression of the Roman city in the films. The study finds that Fellini symbolizes the Roman space with the help of images, realizes the re-creation of the urban space of Rome, and enriches, stimulates and passes on the various cultural memories of the Roman space. At the same time, the study concludes that the film’s retelling of the memory of Roman space is based on director Fellini’s imagination, and it is a unique narrative system of urban images created by integrating history and reality, and it is the result of the joint effect of the iteration of urban time and space and the integration of film narrative.